PVD-Alumina Coatings on Cemented Carbide Cutting Tools: A Study About the Effect on Friction and Adhesion Mechanism - S.E. Cordes (Tribology in Industry, 2012)
Crystalline PVD γ-alumina coatings are interesting for machining operations due to their outstanding characteristics, such as high hot hardness, high thermal stability and low tendency to adhesion. In the present work (Ti,Al)N/γ-Al2O3-coatings are deposited on cemented carbide by means of MSIP. Objectives of this work are to study the effects of coating and cutting fluid regarding friction in tribological tests and to study the wear mechanisms and cutting performance of γ-Al2O3-based coated cemented carbide cutting tools in machining operations of austenitic stainless steels. Based on the remarkable properties of the coating system the performance of the cutting tools is increasing significantly.